LEAFY COTYLEDONs: Connecting different stages of plant development - Chen, Chen; Du, Xinglin (Frontiers in Plant Science, 2022)
The life of higher plants progresses successively through embryonic, juvenile, adult, and reproductive stages. LEAFY COTYLEDON (LEC) transcription factors, first discovered in Arabidopsis thaliana several decades ago, play a key role in regulating plant embryonic development, seed maturation, and subsequent growth. Existing studies have demonstrated that LECs together with other transcription factors form a huge and complex regulatory network to regulate many aspects of plant growth and development and respond to environmental stresses. Here, we focus on the role that has received little attention about the LECs linking different developmental stages and generational cycles in plants. We summarize the current fragmented research progress on the LECs role and molecular mechanism in connecting embryonic and vegetative growth periods and the reproductive stage. Furthermore, the possibility of LECs controlling the maintenance and transition of plant growth stages through epigenetic modifications is discussed.